Bounded learning by doing, inequality, and multi-sector growth: A middle-class perspective (2020)
This paper develops a multi-sector model of middle-class-led economic growth, whereby (i) learning by doing interacts with scale economies and nonhomothetic preferences giving rise to endogenous growth, and (ii) the “middle class” label is an endogenous outcome of the model, depending on past economic growth. The emphasis is placed on the entire income distribution, which affects the composition of demand - range of goods consumed - and in turn, the speed and extent of the learning process in the range of goods produced. Learning is sector specific, bounded from above, and constrained by a minimum scale restriction. It starts with a switch from traditional to modern technologies, understood as structural change. A higher share in the purchasing power of the middle class expands the market size for modern goods, and generates more learning in non-mature modern technologies, contributing to productivity gains, and under certain conditions (e.g. a significant learning potential), to sustained growth. Eventually, we make the case for a strong middle class; that is, redistributive policies towards the middle class and the poor. © 2019 Elsevier Inc.